2019
DOI: 10.15171/ipp.2019.03
|View full text |Cite
|
Sign up to set email alerts
|

Association of CDX2 expression and overall survival and clinicopathologic disease manifestations in patients with gastric cancer in Northwest of Iran

Abstract: Introduction: In the northwest of Iran, gastric cancer is the first and third common form of malignancy in men and women, respectively. Homeobox protein CDX2, was proposed as a prognostic biomarker in gastric cancer. Objectives: This study aimed to assess the association of CDX2 expression overall survival as well as clinicopathologic variables in patients with gastric cancer. Materials and Methods: CDX2 expression was examined by the immunohistochemistry method in the formalin-fixed paraffin-embedded surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Differentiated adenocarcinomas are characterized by higher CDX2 expression than undifferentiated tumors with stronger reactivity in intestinal phenotypes. Some of the latest studies have shown inverse relation between CDX2 expression and depth of invasion and lymphnode metastasis [1]. There is a close correlation between the degree of tumor differentiation and the Ki-67 score (p<0.001) [5].…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Differentiated adenocarcinomas are characterized by higher CDX2 expression than undifferentiated tumors with stronger reactivity in intestinal phenotypes. Some of the latest studies have shown inverse relation between CDX2 expression and depth of invasion and lymphnode metastasis [1]. There is a close correlation between the degree of tumor differentiation and the Ki-67 score (p<0.001) [5].…”
Section: Discussionmentioning
confidence: 95%
“…Stomach cancer incidence rates are much lower in India than elsewhere, but the stomach remains one of the 10 leading sites of cancer in both sexes in most of the metropolitan registries [9]. Gastric carcinoma constitutes the 4 th most common malignancy worldwide with it being 2 nd and 4 th most common reason of malignancy associated death in men and women respectively [1]. Early detection plays a pivotal role in prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations